2011
DOI: 10.1101/gad.2046211
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcription initiation function of the ubiquitous SAGA complex in tissue-specific gene activation

Abstract: The Spt-Ada-Gcn5-acetyltransferase (SAGA) complex was discovered from Saccharomyces cerevisiae and has been well characterized as an important transcriptional coactivator that interacts both with sequence-specific transcription factors and the TATA-binding protein TBP. SAGA contains a histone acetyltransferase and a ubiquitin protease. In metazoans, SAGA is essential for development, yet little is known about the function of SAGA in differentiating tissue. We analyzed the composition, interacting proteins, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 51 publications
5
83
2
4
Order By: Relevance
“…Thus, cell-specific effects of recessive lethal alleles can be examined in the embryonic or larval stages, prior to the stage of lethality. This genetic technique has been previously used to positively label cells in embryonic muscle that were homozygous for mutations in the SAGA subunit, sgf11 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cell-specific effects of recessive lethal alleles can be examined in the embryonic or larval stages, prior to the stage of lethality. This genetic technique has been previously used to positively label cells in embryonic muscle that were homozygous for mutations in the SAGA subunit, sgf11 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Methods to isolate cells from intact tissues include laser microdissection, and fluorescence-activated cell sorting (FACS) of whole cells. While FACS has been used to isolate cells and nuclei from Drosophila embryos and from Caenorhabditis elegans for gene expression and chromatin profiling [1][2][3] , FACS and laser microdissection can be difficult to perform successfully in tissues that contain highly intermixed cell types or that contain cells with irregular morphology, such as neurons. To overcome this difficulty, nuclei rather than cells can be isolated from specific cell types and used for subsequent gene expression profiling.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide location studies of SAGA complex subunits in different organisms reached various conclusions as to the extent of SAGA binding; while some reported only a few hundred binding sites for SAGA subunits, mainly at a subset of promoters, others observed more wide-spread occupancy. 22,23,24,25,26 Bonnet et al recently confirmed that SAGA deubiquitylates H2B in the coding region of all expressed genes in yeast and human cells-whereas earlier studies reached their conclusions by inspecting the occupancy of SAGA subunits, Bonnet et al examined deubiquitylase activity by measuring H2Bub distribution in the coding regions of active genes upon disruption of SAGA. 8 Earlier studies that concluded that SAGA is associated with a subset of active genes may have detected only the most stable interactions of the examined SAGA subunit with DNA.…”
Section: Saga Regulates Genome-wide Transcriptionmentioning
confidence: 97%
“…8 Increasingly, however, evidence has indicated that regulation of SAGA in multicellular organisms involves more sophisticated mechanisms than in their unicellular counterparts. 9,10 In order to gain more insight into SAGA function in multicellular eukaryotes, we turned to Drosophila. This model provided powerful genetic and biochemical tools in which to explore principles underlying SAGA-mediated gene regulation.…”
Section: 2mentioning
confidence: 99%